Effects of passive and active rest on physiological responses and time motion characteristics in different small sided soccer games - Arslan, E.; Alemdaroglu, U.; Koklu, Y.; Hazir, T.; Muniroglu, S.; Karakoc, B. (Journal of Human Kinetics, 2017)
The purpose of this study was to investigate the effects of resting regimes on physiological responses and time motion characteristics between bouts during small sided games (SSGs) in young soccer players. Sixteen players (average age 16.87 ± 0.34 years; body height 176.69 ± 3.21 cm; body mass 62.40 ± 2.59 kg; training experience 3.75 ± 0.44 years) performed four bouts 2-a-side, 3-a-side and 4-a-side games with three minutes active (SSGar: Running at 70% of HRmax) and passive (SSGpr) rest between bouts at two-day intervals. The heart rate (HR) along with total distance covered in different speed zones - walking (W, 0-6.9 km·h-1), low-intensity running (LIR, 7.0-12.9 km·h-1), moderate-intensity running (MIR, 13.0-17.9 km·h-1) and high-intensity running (HIR, >18km·h-1), were monitored during all SSGs, whereas the rating of perceived exertion (RPE, CR-20) and venous blood lactate (La-) were determined at the end of the last bout of each SSG. The results demonstrated that all SSGpr elicited significantly higher physiological responses compared to SSGar in terms of the RPE and La- (p < 0.05). In addition, 2-a-side SSGpr induced significantly lower %HRmax responses and total distance covered than 2-a-side SSGar (p < 0.05). Moreover, the distance covered at HIR was significantly higher in 4-a-side SSGar than 4-side SSGpr. The results of this study indicate that both SSGs with passive and active rest can be used for soccer specific aerobic endurance training. Furthermore, all SSGs with active recovery should be performed in order to increase players and teams` performance capacity for subsequent bouts.